2012
DOI: 10.1088/0031-9155/57/10/3207
|View full text |Cite
|
Sign up to set email alerts
|

A bone marrow toxicity model for223Ra alpha-emitter radiopharmaceutical therapy

Abstract: Purpose Ra-223, an α-particle emitting bone-seeking radionuclide, has recently been used in clinical trials for osseous metasteses of prostate cancer. We investigated the relationship between absorbed fraction-based red marrow dosimetry and cell level-dosimetry using a model that accounts for the expected localization of this agent relative to marrow cavity architecture. We show that cell level-based dosimetry is essential to understanding potential marrow toxicity. Methods The GEANT4 software package was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 32 publications
7
100
1
1
Order By: Relevance
“…Absorbed doses are primarily delivered to the red marrow from circulating blood and from uptake on the bone surfaces. However, a emissions will irradiate only a small fraction of the red marrow because of their short range (28). The absorbed dose delivered from the circulating activity may therefore be a more relevant guide to the potential for marrow toxicity than that due to activity on the bone surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Absorbed doses are primarily delivered to the red marrow from circulating blood and from uptake on the bone surfaces. However, a emissions will irradiate only a small fraction of the red marrow because of their short range (28). The absorbed dose delivered from the circulating activity may therefore be a more relevant guide to the potential for marrow toxicity than that due to activity on the bone surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The physically larger alpha particle manifests a shallow penetration until the cortical bone region where the metastases should be located (64). In their model, for the estimation of osseous radiation absorption, Hobbs et al attested that the majority of radiation dose is deposited near the trabecular elements (65). Moreover, dosimetric considerations indicated that assuming a 0.67 Bq/mm 2 dose of 223 Ra on the surface of a sphere with 250 μm radius, the estimated absorbed dose quickly decreased from 65 Gy to 0 Gy at from 5 μm to 70 μm deep, respectively.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…The high linear energy transfer of a radiation results in a greater biologic effectiveness than b radiation, as well as generation of double-strand DNA breaks, and gives rise to cytotoxicity that is independent of dose rate, cell cycle growth phase, and oxygen concentration (19). The range of the a particles (,100 mm) is much smaller than the 0.7-cm path length of 89 Sr and the 0.33-cm path length of 153 Sm; as a result, less hematologic toxicity for a given bone surface dose would be expected from a emitters than from b emitters (20). It is estimated that as few as 1-20 a tracks crossing the nucleus will result in cell death (19).…”
Section: Ra-dichloridementioning
confidence: 99%
“…Hobbs et al estimated the percentage of cells that receive a potentially toxic absorbed dose (2 or 4 Gy). On the basis of the model, it is estimated that the majority of the radiation dose is deposited near the trabecular elements, substantially decreasing the risk of marrow toxicity at higher doses (20). Using an International Commission on Radiological Protection biokinetic model for alkaline earth elements, Lassman et al estimated the absorbed dose to organs from 223 Ra.…”
Section: Dosimetry and Toxicitymentioning
confidence: 99%
See 1 more Smart Citation